Analisis Sistem Manajemen Kelas melalui Strategi Pengaturan Waktu sebagai Kunci Pembelajaran Berkualitas - Maharika, Mayang; Lajuardi, Arini Maulidiya; Wulandari, Febby Putri; Bektiarso, Singgih (Journal of Health, Education, Economics, Science, and Technology, 2025)
Effective classroom management, particularly in time management, plays a crucial role in creating a quality learning environment. This article analyzes time management strategies that teachers can implement to enhance learning effectiveness, including prioritization, time blocking methods, and daily scheduling. The research employs a literature review to identify challenges arising from both internal factors (teacher competence and student motivation) and external factors (education policies and facility availability). The findings suggest that technology, such as LMS platforms and time management applications, can significantly improve time management efficiency in the classroom. By applying the right strategies, effective time management can increase student participation, discipline, and overall learning outcomes, both in face-to-face and online learning environments.